1993
DOI: 10.1002/ajpa.1330920305
|View full text |Cite
|
Sign up to set email alerts
|

Growth of nomadic and settled Turkana infants of northwest Kenya

Abstract: Turkana tribespeople reside in a semi-arid savanna ecosystem in northwest Kenya. For over a decade, Ngisonyoka Turkana nomads have been studied within a multidisciplinary framework that embraces ecology, anthropology, and human population biology. Original research objectives of the South Turkana Ecosystem Project were to study nomads longitudinally and within the context of the dry savanna ecosystem. These objectives have been expanded to incorporate settled Turkana who were nomads in the recent past, but who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

1994
1994
2008
2008

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 21 publications
1
22
0
Order By: Relevance
“…First and foremost, we think that these socioeconomic and biological differences reflect underlying changing dietary regimes. Pastoral diets are generally characterized as high in protein but low in calories, with marked seasonal variation in both protein and energy content (Galvin, 1985(Galvin, , 1992Galvin and Little, 1999;Little et al, 1993;Nathan et al, 1996;Nestel, 1986;Shell-Duncan, 1995). The lean seasons for Ariaal and Rendille pastoralists come at the end of the two dry seasons (NovemberMarch and May-August) when livestock pasture becomes scarce, in turn limiting both drinking water and milk availability for human consumption (Fratkin, 1991).…”
Section: Sedentarization As Changing Patterns Of Diet Seasonalty Momentioning
confidence: 98%
“…First and foremost, we think that these socioeconomic and biological differences reflect underlying changing dietary regimes. Pastoral diets are generally characterized as high in protein but low in calories, with marked seasonal variation in both protein and energy content (Galvin, 1985(Galvin, , 1992Galvin and Little, 1999;Little et al, 1993;Nathan et al, 1996;Nestel, 1986;Shell-Duncan, 1995). The lean seasons for Ariaal and Rendille pastoralists come at the end of the two dry seasons (NovemberMarch and May-August) when livestock pasture becomes scarce, in turn limiting both drinking water and milk availability for human consumption (Fratkin, 1991).…”
Section: Sedentarization As Changing Patterns Of Diet Seasonalty Momentioning
confidence: 98%
“…Mortality in the first few days of life is strongly associated with the intrauterine experience. Pike (1996) found that perinatal (Gray, 1999;Little et al, 1993;Pike, 1996). This increased vulnerability at 4-6 months is not associated with any clear changes in an infant's diet or caretaking, but may be evidenced by the substantial number of deaths occurring prior to crawling.…”
Section: Discussionmentioning
confidence: 93%
“…Briefly, Turkana children who were measured in this period tended to be small at birth but grew rapidly in their first 6-8 months, when they compared favorably with international growth standards. After this age and through the beginning of their third year, they experienced a marked deceleration in growth velocity, which was more pronounced for weight than for stature (Little et al, 1983(Little et al, , 1993Little and Gray, 1990;Gray, 1996Gray, , 1998Pike, 1996). In middle and late childhood, Turkana boys and girls were small and thin for their age; typically, they were below the 5th percentile of international growth standards in both weight and stature until puberty (Little and Johnson, 1987;Little and Gray, 1990), when they appeared to ''shift'' from below the 5th percentile of international standards for stature (Hammill et al, 1979) to between the 25th and 50th percentiles.…”
Section: Growth Of Pastoralist Children In Northeastmentioning
confidence: 97%